Lengthening the Lifetime of Common Emissive Probes to Microseconds by a Jigsaw‐Like Construction of NIR‐Responsive Nanohybrids. Issue 8 (24th February 2020) - Estebanez, Nestor; Ferrera‐González, Juan; Cortez‐Cevallos, Ian Alberto; González‐Béjar, María; Pérez‐Prieto, Julia
Abstract: Chemical/biological sensing by means of luminescence still requires improvement of signal contrast and depth of sample imaging. Though there is a considerable number of emissive molecular and quantum dot probes, most of them absorb in the UV–vis range and emit in the visible and exhibit emission lifetime in the nanoscale. Optical bioimaging in the near infrared window based on these dyes offers reduced light scattering, lower competitive absorption, and reduced background autofluorescence, but it requires a high‐power pulsed laser. An approach to lengthening the emission lifetime of common fluorophores/probes is presented. It consists of coupling them to lanthanide‐based upconversion nanoparticles (UCNPs) via an easy, jigsaw‐like strategy. As a proof of concept, nanohybrids comprising UCNPs attached to fluorescein (a well‐known pH sensor) are prepared by connecting the key pieces through ionic interactions, i.e., without using any other reagents. Fluorescence imaging of the nanohybrids clearly shows the co‐occurrence of the UCNP and the chemical probe and as a consequence the long‐lived fluorescence of the probe due to resonance energy transfer from the UCNP. This strategy opens up endless possibilities to prepare new nanohybrids by selecting the key jigsaw pieces to exploit the color emission of common probes. Abstract : A jigsaw construction can be applied to enable co‐occurrence of upconversion nanoparticles (UCNPs) and dyes and to lengthen the dye lifetime to microseconds. Nanohybrids consisting of UCNPs spaced at a fixed short distance from common emissive dyes are prepared by using a rigid macrocycle (cucurbituril) and a lanthanide trication, all these pieces simply connected by ionic interactions.